MEASURMENT ERROR EFFECT ON THE POWER OF CONTROL CHART FOR ZERO TRUNCATED NEGATIVE BINOMIAL DISTRIBUTION (ZTNBD) - Khurshid, Anwer (Yugoslav Journal of Operations Research, 2017)
In the present article measurement error effect on the power of control chart for ZTNBD is investigated based on standardized normal variate. Numerical calculations are presented to understand the consequences of measurement errors on the power curve. To examine the sensitivity of the monitoring procedure, average run length (ARL) is also considered.